VITAMIN D PROVISION OF GIRLS WITH MENSTRUAL DISORDERS - Makhfuza Mubinovna Rakhmatullaeva; Shakhnoza Ulug’bekovna Sharipova (Scholar Express Journals, 2022)
Despite the fact that the effect of vitamin D deficiency on the health of children and adolescents has been studied for a long time, information about the role of vitamin D in the formation of menstrual function in puberty girls is few and ambiguous. There is a close relationship between vitamin D deficiency and various other factors that determine a wide range of polymorphic clinical manifestations in which menstrual dysfunction is essential in puberty girls. Vitamin D deficiency was detected in girls with menstrual disorders, correction of the level of which led to normalization of the menstrual cycle in 78.1% of girls. Thus, vitamin D supplementation corrects menstrual dysfunction, and therefore, vitamin D can be recommended for use in combination in the treatment and prevention of menstrual disorders.
Keywords: Menstrual dysfunction; girls; vitamin D deficiency; prevention of menstrual disorders